Assessing minimum environmental flows in nonpermanent rivers: The choice of thresholds. (May 2016) - Aguilar, Cristina; Polo, María José
Abstract: The criteria used in the computation of the minimum environmental flow regime and flow cessation periods in nonpermanent rivers are often left to open criteria. This study proposes a stochastic approach for evaluating the choice of local thresholds in the characterization of minimum environmental flows through both the Monte Carlo technique and local hydrological relationships. This approach is applied to four regimes obtained by hydrologic and hydraulic habitat modeling in a Mediterranean watershed. The operationality, defined as the probability of the calculated environmental regime being satisfied by the natural regime over 25 years, was assessed for eight different scenarios. Two monthly minimum environmental flow regimes were then generated, with 90 and 95% operationality levels. This analysis allows the generation of minimum flow regime prescriptions from a strictly hydrologic point of view. The methodology proposed constitutes a useful tool for the implementation of uncertainty analysis of environmental flows in water resource management. Highlights: Minimum environmental flows are sensitive to thresholds applied in the calculations. We propose a stochastic approach for determining local thresholds. Optimization was applied to give prescriptions based on an operationality assessment. A tool for the uncertainty assessment required in risk analysis is provided.